Collaborative Governance of Rural and Urban Land and Building Tax (PBB-P2) Management in Makassar City - M, Nursafitra; Akib, Haedar; Jayadi, Karta (International Journal of Education, Management, and Technology, 2025)
This study aims to analyze the determinants that influence Collaborative Governance of Rural and Urban Land and Building Tax Management (PBB-P2) in Makassar City using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) approach. Existence of collaborative governance PBB-P2 in Makassar City carried out by the Makassar City Regional Revenue Agency (Bapenda) with stakeholders runs more effectively and is able to increase taxpayer compliance in increasing local revenue. One of the success factors of collaboration of a government organization or agency depends on the resources it has and the support of the internal and external environment that affects it. This research uses a qualitative descriptive approach method with data collection through observation, interviews and document review. The results showed that the determinants that influence Collaborative Governance of Rural and Urban Land and Building Tax Management (PBB-P2) in Makassar City are commitment between actors, trust, technological innovation and information systems, and communication. Strategies to utilize strengths to overcome threats to strengthen collaboration through the commitment of the Makassar City Government and the utilization of technology and information systems in the management of PBB-P2 in Makassar City, Strategies to overcome weaknesses and face threats through the placement of human resources of Bapenda Makassar City in accordance with their respective fields of expertise managing taxes and increasing public trust in tax management in Makassar City, Strategies to overcome weaknesses and face threats through collaboration and technological innovation in the management of PBB-P2 in Makassar City and the development of community participation as taxpayers.